Nature and degree of aqueous alteration in CM and CI carbonaceous chondrites. (12th August 2013) - Takir, Driss; Emery, Joshua P.; Mcsween, Harry Y.; Hibbitts, Charles A.; Clark, Roger N.; Pearson, Neil; Wang, Alian
Abstract: We investigated the petrologic, geochemical, and spectral parameters that relate to the type and degree of aqueous alteration in nine CM chondrites and one CI (Ivuna) carbonaceous chondrite. Our underlying hypothesis is that the position and shape of the 3 μm band is diagnostic of phyllosilicate mineralogy. We measured reflectance spectra of the chondrites under dry conditions (elevated temperatures) and vacuum (10 −8 to 10 −7  torr) to minimize adsorbed water and mimic the space environment, for subsequent comparison with reflectance spectra of asteroids. We have identified three spectral CM groups in addition to Ivuna. "Group 1, " the least altered group as determined from various alteration indices, is characterized by 3 μm band centers at longer wavelengths, and is consistent with cronstedtite (Fe‐serpentine). "Group 3, " the most altered group, is characterized by 3 μm band centers at shorter wavelengths and is consistent with antigorite (serpentine). "Group 2" is an intermediate group between group 1 and 3. Ivuna exhibits a unique spectrum that is distinct from the CM meteorites and is consistent with lizardite and chrysotile (serpentine). The petrologic and geochemical parameters, which were determined using electron microprobe analyses and microscopic observations, are found to be consistent with the three spectral groups. These results indicate that the distinct parent body aqueous alteration environments experienced by these carbonaceous chondrites can be distinguished using reflectance spectroscopy. High‐quality ground‐based telescopic observations of Main Belt asteroids can be expected to reveal not just whether an asteroid is hydrated, but also details of the alteration state.